Digital Volumetric Monitoring of Palate Growth in Children With Cleft Lip and Palate. Issue 2 (11th March 2022) - Ambrosio, Eloá Cristina Passucci; Fusco, Nathália dos Santos; Carrara, Cleide Felício Carvalho; Bergamo, Mariel Tavares; Lourenço Neto, Natalino; Cruvinel, Thiago; Rios, Daniela; Almeida, Ana Lucia Pompeia Fraga; Soares, Simone; Machado, Maria Aparecida Andrade Moreira; Oliveira, Thais Marchini
Abstract : Abstract: This study aimed to evaluate longitudinally the volume of the dental arches in children with unilateral cleft lip and palate before and after the rehabilitative plastic surgeries. This is a longitudinal retrospective study was composed by 102 digitized dental casts of children with unilateral complete cleft lip (G1) and cleft lip and palate (G2). The palate volume was evaluated at 3 periods: preoperative (T1), postoperative 1 (T2), and postoperative 2 (T3). The intra- and inter-examiner reliability was analyzed by Wilcoxon test/Dahlberg formula and interclass correlation coefficient, respectively. The intragroup comparison was analyzed by Wilcoxon test and Friedman test followed by post-hoc Dunn test. Mann–Whitney test was applied for the intergroup comparison (α = 5%). G1 had a significant growth at T2 ( P = 0.031). G2 demonstrated a positive development at T2, but decreased at T3 ( P = 0.003). The intergroup analysis revealed that G2 showed a greater volume at T1 and T2 ( P < 0.0001 and P = 0.0024, respectively). T2-T1 exhibited no statistically significant difference ( P = 0.262). In conclusion, there was a volumetric increase in the dental arches after cheiloplasty followed by a reduction after palatoplasty. Further investigations are necessary to validate the preliminary results of the present study.